2014
DOI: 10.1111/mam.12026
|View full text |Cite
|
Sign up to set email alerts
|

Using occupancy analysis to validate the use of footprint tunnels as a method for monitoring the hedgehog Erinaceus europaeus

Abstract: Indirect survey methods are often used in studies of mammals, but are susceptible to biases caused by failure to detect species where they are present. Occupancy analysis is an analytical technique which enables non-detection rates to be estimated and which can be used to develop and refine novel survey methods. In this study, we investigated the use of footprint tunnels by volunteers as a method for surveying occupancy of sites by hedgehogs Erinaceus europaeus. The survey protocol led to a very low non-detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…We found that using an indirect sign survey was suitable for estimating the occupancy of Chinese pangolin to address the problem of inadequate direct sightings. To validating the indirect sign and survey especially for the study of mammals, occupancy models are considered a powerful approach (Yarnell et al, 2014). However, our survey did not meet the assumption of abundance models of occupancy (Conroy, Runge, Barjer, & Schofield, 2008; Nichols, Hines, MacKenzie, Seamans, & Guiterrez, 2007; Royle & Nichols, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We found that using an indirect sign survey was suitable for estimating the occupancy of Chinese pangolin to address the problem of inadequate direct sightings. To validating the indirect sign and survey especially for the study of mammals, occupancy models are considered a powerful approach (Yarnell et al, 2014). However, our survey did not meet the assumption of abundance models of occupancy (Conroy, Runge, Barjer, & Schofield, 2008; Nichols, Hines, MacKenzie, Seamans, & Guiterrez, 2007; Royle & Nichols, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of suitable release sites for rehabilitated hedgehogs, with optimal release sites being those that are suburban and free of badgers. This is borne out by current research in the UK showing that hedgehog occupancy and abundance is low in rural landscapes (Hubert et al 2011;Yarnell et al 2014;Pettett et al 2017;Williams et al 2018;Williams et al 2018a), which suggests that these habitats are sub-optimal for hedgehogs and should not be used for rehabilitation release and that release into suburban areas without main roads and badgers should increase individual survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…For all three studies, training material and workshops were developed by the researchers and provided to students and teachers prior to the actual field research. Hands‐on activities such as setting up hedgehog footprint tracking tunnels (Yarnell et al., ) and identification trainings for birds and butterflies as well as methods on how to observe animals and to follow standardised protocols were taught to students and teachers before the start of their participation.…”
Section: Case Studiesmentioning
confidence: 99%
“…Hands-on activities such as setting up hedgehog footprint tracking tunnels (Yarnell et al, 2014) and identification trainings for birds and butterflies as well as methods on how to observe animals and to follow standardised protocols were taught to students and teachers before the start of their participation.…”
Section: Students As Reliable Observers and Multipliers In Wildlifementioning
confidence: 99%